Aboveground Competition and Herbivory Overpower Plant-Soil Feedback Contributions to Succession in a Remediated Grassland - Dietterich, Lee H.; Li, Amy; Garvey, Sarah M.; Casper, Brenda B. (Frontiers in Ecology and Evolution, 2019)
Plant-soil feedback (PSF) can provide a driving force during ecological succession by altering soil properties in ways that benefit or disadvantage other species in the successional sequence. Succession may be inevitable in disturbed sites remediated by planting early successional species, but information on PSF in such settings is lacking. We investigated whether gray birch (Betula populifolia), a native pioneer tree, alters succession from grassland to deciduous forest at a site contaminated with zinc, lead, and cadmium. We investigated PSF within the context of competition, herbivory, and soil contaminants, and evaluated whether gray birch, as a metal accumulator, engages in elemental allelopathy, poisoning other species through its metal-contaminated leaf litter. We assessed effects of gray birch on neighboring plant community structure, soil chemistry, fungal root symbionts, and germination, growth, and herbivory of seedlings of black oak (Quercus velutina) and sugar maple (Acer saccharum), two tree species expected to follow gray birch in succession. Gray birch was associated with increased diversity in its neighborhood grassland community, increased herbivory on black oak seedlings, and influenced root fungal colonization in both species. Seedling biomass was correlated with colonization by ectomycorrhizal fungi in black oak, but not with arbuscular mycorrhizal or dark septate fungal colonization in sugar maple. Gray birch had no effect on maple seedling performance or soil chemistry, and a small effect on oak performance in the absence of aboveground competition. We found little evidence consistent with elemental allelopathy. Oak and maple seedlings responded more strongly to variation in soil nutrients than heavy metals, and maintained leaf metal concentration profiles markedly different from those in soils. We conclude that gray birch alters its environment in ways that could promote establishment and succession of woody species, potentially favoring ectomycorrhizal species, but most effects of PSF are overpowered by aboveground competition, herbivory, and/or existing soil factors. This study well illustrates why potential PSF effects on plant performance and community structure must be examined within the context of other ecological processes. Such a broad understanding can inform decisions made in remediation and management of disturbed sites, and our understanding of plant succession and coexistence in general.